SUSCEPTIBILITY OF SORGHUM CULTIVARS TO SITOPHILUS ORYZAE L. (COLEOPTERA: CURCULIONIDAE) DURING STORAGE - Hendrival, Hendrival; Putra, Rengga Laksamana; Aryani, Dewi Sartika (Universitas Muhammadiyah Yogyakarta, 2019)
Sitophilus oryzae L. is a primary pest that causes damage to stored sorghum. The aim of this study was to evaluate the susceptibility of some sorghum cultivars to S. oryzae infestations and the damage resulted during storage period. The research was carried out at Plant Pest and Disease Laboratory, Department Agroecotechnology, Faculty of Agriculture, Malikussaleh University from February to June 2017. Nine cultivars of sorghum were screened for their susceptibility to S. oryzae attacks and the damage resulted. The Dobie sesceptibility indexwas used to classify the susceptibility of sorghum cultivars. Susceptibility experiment of several sorghum cultivars to S. oryzae was done by no choice assay. The results exhibited that sorghum cv. Suri 3, Suri 4, Kawali, and Numbu was categorized as moderate. Cv. Samurai 1 was included in moderate to susceptible, and cv. Super 1, Super 2, Samurai 2, and Pahat were categorized as susceptible to S. oryzae. The susceptibility of sorghum cultivars was determined by high number of F1 progeny, the high percentage of seed weight loss, damaged seeds, low median development time and low width of sorghum seeds.